Counseling on vegetable cultivation with hydroponics to increase food security during the Covid-19 pandemic - Aisyah Cinta Putri Wibawa; Syifaul Fuada; Nuur Wachid Abdul Majid; Hashina Qiamu Mumtaziah; Ratih Suci Aryanti (Community Empowerment, 2023)
The Covid-19 pandemic caused Wanajaya Village to experience quarantine and caused a scarcity of food supplies, especially vegetables. This counseling activity aims to help the community of Villa Mutiara Housing RT 002/013, Cibitung, Bekasi, West Java in understanding the potential that exists to meet food needs through hydroponic vegetable cultivation. Vegetable cultivation activities with hydroponics are carried out in several stages including preparation, socialization, implementation, and evaluation. The results of this community service activity include increasing public understanding of the importance of consuming vegetables and meeting the need for vegetables to maintain family food supplies during the quarantine period.